PENGUATAN KINERJA MARKETING PERBANKAN MELALUI PENGELOLAAN STRES KERJA, BEBAN KERJA, DAN KOMITMEN KERJA PADA PT BANK RAKYAT INDONESIA CABANG GOWA - Hendra Gunawan (Universitas Ichsan Sidenreng Rappang, 2022)
This study aims to analyze the influence of job stress, workload, and work commitment on marketing performance at PT Bank Rakyat Indonesia, Gowa Branch. This research employed a quantitative approach with an explanatory research design. The sample consisted of 105 marketing employees who were directly involved in banking product marketing activities, target achievement, customer service, and business relationship management with customers. Data were collected through questionnaires and analyzed using SPSS through validity testing, reliability testing, classical assumption testing, multiple linear regression, partial testing, simultaneous testing, and coefficient of determination analysis. The results show that job stress has a negative but insignificant effect on marketing performance. This indicates that the work pressure experienced by marketing employees has not become a major factor that directly determines performance decline. Workload has a positive and significant effect on marketing performance, meaning that a directed and manageable workload can encourage employee productivity. Work commitment also has a positive and significant effect on marketing performance and becomes the most dominant variable in explaining performance improvement. These findings confirm that strengthening marketing performance in the banking sector cannot rely solely on controlling work pressure, but must also be supported by proportional workload management and stronger employee commitment to the organization. This study provides practical implications for banking management in developing a healthy, productive, and sustainable marketing work system.